Choosing the right tree variety to avoid attack by psyllids - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
In the mid-1980s the leucaena psyllid struck south-east Asia causing widespread defoliation. The leucaena variety K8, which was the most widely planted cultivar at that time, was particularly susceptible to attack. An international conference and...